Unveiling the oxidation behavior of liquid-phase exfoliated antimony nanosheets - Assebban, Mhamed; Gibaja, Carlos; Fickert, Michael; Torres, Inigo; Weinreich, Erik; Wolff, Stefan; Gillen, Roland; Maultzsch, Janina; Varela, Maria; Rong, Sherman Tan Jun; Loh, Kian Ping; Michel, Enrique G.; et al. (2D Materials, 2020)
Antimonene, a monolayer of beta-antimony, is increasingly attracting considerable attention, more than that of other monoelemental two-dimensional materials, due to its intriguing physical and chemical properties. Under ambient conditions, antimonene exhibits a high thermodynamic stability and good structural integrity. Some theoretical calculations predicted that antimonene would have a high oxidation tendency. However, it remains poorly investigated from the experimental point of view. In this work, we study the oxidation behavior of antimonene nanosheets (ANS) prepared by ultrasonication-assisted liquid-phase exfoliation. Using a set of forefront analytical techniques, a clear effect of sonication time on the surface chemistry of prepared ANS is found. A dynamic oxidation behavior has been observed, which upon annealing at moderate temperature (210 degrees C) resulted in a semiconducting behavior with a bandgap of approximately 1 eV measured by ultraviolet photoelectron spectroscopy. This study yields valuable information for future applications of antimonene and paves the way towards novel modification approaches in order to tailor its properties and complement its limitations.
CRIS-Team WoS Importer:2020-04-07